Targeting the Tumor: Molecular Pathways and Therapeutic Frontiers in Breast Cancer - Tarique, Mohammed; Sindi, Abdulmajeed Abdulghani Abdulmajeed; Helmi, Nawal; Alam, Qamre (International Journal of Pharmaceutical Investigation, 2026)
Breast Cancer (BC) is the leading cause of mortality in the majority of women around the globe. It stands as one of the most common types of cancer after non-melanoma skin cancer. Contemporary oncology distinguishes BC utilizing molecular markers into three subtypes – invasive, non-invasive, and metastatic, out of which invasive ductal carcinoma is the most common. These subtypes of BC are determined by their assessment of hormone receptors (ER/PR), HER2 status, and proliferation biomarkers (Ki-67), which directs therapeutic decision-making in context of the treatment to be provided to the patient. Prevalent Signature biomarkers help detect the type of BC, the stage, and its status (benign or metastatic), the treatment to be provided, and targeted therapeutics to cure and prevent its recurrence. Oncogenesis in breast cancer is a result of aberrant and disrupted signalling pathways. Novel therapies are designed to reduce the risk of cancer providing a prolonged survival. Understanding the molecular mechanism can help aid the desired therapeutics for the next generation with more focus on reducing the toxicity and enhancing the efficacy of the drugs administered. This review aims to provide a collaborative preview of the signaling pathways utilized in breast cancer, precision medicine in oncology and targeted or combined therapeutics as emerging innovative treatment for the upcoming generations.
Keywords: Cancer; Molecular markers; Oncogenesis; Precision medicine signaling pathways; Therapeutics